Pengaruh Fraud Diamond terhadap Finansial Statement Fraud pada Perusahaan Farmasi di Bursa Efek Indonesia Tahun 2021-2023 - Eliza Paskah Lestari Gunantoro; Risawati Risawati (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research investigates the influence of the fraud diamond on financial statement fraud in pharmaceutical firms listed on the Indonesia Stock Exchange for the period 2021-2023. A purposive sampling method was used, resulting in a selection of 12 companies. The study relies on secondary data, which was gathered through documentation from the official website www.idx.co.id. To analyze the data, the research employs descriptive statistical analysis, classical assumption tests, determination tests, t-tests, and multiple linear regression analysis using SPSS 27 software. The findings reveal that the Nature of Industry significantly affects financial statement fraud, while other factors, including Financial Targets, Changes in Auditors, and Switches in Direction, do not have a significant impact on financial statement fraud. These results suggest that industry characteristics play a crucial role in shaping the likelihood of financial statement manipulation. Pharmaceutical companies with specific industry dynamics may face different pressures, which can influence their financial reporting practices. On the other hand, financial targets, auditor changes, and management changes do not appear to have a substantial direct impact, indicating that other factors not covered in the study might be influencing financial fraud behaviors. This study provides valuable insights for regulators, auditors, and stakeholders in the pharmaceutical sector to better understand the risk factors associated with financial statement fraud.